EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN KACANG HIJAU (Vigna radiata L.) DI KECAMATAN TABONGO KABUPATEN GORONTALO - Syenyantri, Syenyantri; Azis, Muhammad Aref; Rahman, Rival (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2025)
The growth of mung beans needs to increase plant productivity by evaluating land suitability for maximum results. The study aimed to determine the characteristics and quality of land and land suitability classes and limiting factors for developing mung bean plants in the Tabongo Subdistrict. The study was conducted from February to May 2024 in the Tabongo Subdistrict of Gorontalo Regency. The study used a matching method between the quality and characteristics of the Tabongo Subdistrict land with the criteria for land suitability for mung bean plants to produce actual land suitability classes and potential land suitability classes. Data was processed by analyzing land quality, characteristics, and suitability classes. The study's results showed that the actual land suitability class for green beans was dominated by class S3 (marginally suitable) and N (Not Suitable) with each class having different sub-classes, namely S3tc,wa,na,eh covering an area of 778.38 ha (74.70%), S3tc,wa,na covering an area of 176.31 ha (16.92% and S3tc,wa,rc,na with an area of 48.75 ha (4.68%). This class has limiting factors of temperature, water availability, rooting media, Available Nutrients, Erosion hazards, and Land preparation. Class S3 also dominated the potential land suitability class with an area of 1003.44 ha and N covering an area of 38.61 ha. It can be concluded that the land suitability class for green beans in the Tabongo sub-district is quite large, dominated by the marginally suitable class (S3) of 96.29%, and the remaining 3.71% have land suitability class N (Not Suitable).